2004
DOI: 10.1103/physrevlett.93.140407
|View full text |Cite
|
Sign up to set email alerts
|

Gisin's Theorem for Three Qubits

Abstract: We present a Theorem that all generalized Greenberger-Horne-Zeilinger states of a three-qubit system violate a Bell inequality in terms of probabilities. All pure entangled states of a three-qubit system are shown to violate a Bell inequality for probabilities; thus, one has Gisin's theorem for three qubits.PACS numbers: 03.65. Ud, 03.67.Mn, Quantum mechanics violates Bell type inequalities that hold for any local-realistic theory [1,2,3,4,5]. In 1991, Gisin presented a theorem, which states that any pure enta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
94
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 26 publications
(25 reference statements)
2
94
0
Order By: Relevance
“…An important approach to characterize entanglement is Bell inequality [3][4][5][6][7][8]. For instance, N. Gisin has proved that all two-qubit pure entangled states violate the CHSH inequality [4].…”
Section: Introductionmentioning
confidence: 99%
“…An important approach to characterize entanglement is Bell inequality [3][4][5][6][7][8]. For instance, N. Gisin has proved that all two-qubit pure entangled states violate the CHSH inequality [4].…”
Section: Introductionmentioning
confidence: 99%
“…Soon after, Gisin and Peres provided an elegant proof of this theorem for the case of pure two-qudit systems [24]. Chen et al showed that all pure entangled three-qubit states violate a Bell inequality [25]. Nevertheless, it still remains open whether Gisin's theorem can be generalized to the multi-qudit case.…”
mentioning
confidence: 99%
“…For the three-qubit case, such a difficulty has been overcome in Ref. [11], where a probabilistic Bell inequality was proposed and consequently Gisin's theorem for three qubits naturally returned. Recent development also indicates that Bell inequality is not unique when one studies Gisin's theorem for three qubits, in Ref.…”
mentioning
confidence: 99%